INFLUENCE OF PLANT GROWTH PROMOTING SUBSTANCES IN MICROPROPAGATION OF STRAWBERRY CV. FESTIVAL - S. DIENGNGAN; B. N. S. MURTHY (The Bioscan, 2014)
Strawberry cv. Festival nodal segments were excised and cultured for 21 days on the initiation medium supplemented with various levels of BAP and TDZ. Subculture was performed and finally rooting was instigated on the medium supplemented with IBA for 4 weeks. The upshots revealed that, shoot proliferation percentage was maximum in MS medium supplemented with 0.5 mg/L TDZ at 100%. The maximum number of shoots per explant and shoot length was obtained in MS medium supplemented with 1mg/L TDZ at 6.40±0.37 and 3.50±0.07 cm respectively, whereas, minimum number of days to shoot initiation was obtained in MS medium supplemented with TDZ 0.5 and BAP 1.5 mg/L at 8.40±0.40 and 8.40±0.31 days respectively. MS medium supplemented with 0.5 mg/L IBA unveiled highest percentage of rooting at 100%, however, highest number of roots per microcutting at 5.00±0.21, maximum root length of microcuttings at 3.25±0.10 cm and minimum number of days to root initiation at 9.80±0.29 was obtained in medium supplemented with 1mg/L IBA.